El seminario “Historia de la Matemática” y su papel en la formación de docentes (ING) - Chaves Barboza, Eduardo (Uniciencia, 2008)
This article describes mission, objectives and used methodology of the SEMINARY, and the results obtained by the participant students. After that, some recommendations are offered to develop investigation in the mathematical history application like a methodological resource, and it gives emphasis to didactic importance in the Mathematicʼs History courses of the universities.